2021
DOI: 10.1097/md.0000000000025483
|View full text |Cite
|
Sign up to set email alerts
|

The association between interleukin-8 gene-251 A/T polymorphism and sepsis

Abstract: Background: Emerging evidence has indicated that interleukin-8 (IL-8) gene-251A/T polymorphism may affect individual susceptibility to sepsis. However, the results of published studies are inconclusive. The aim of this meta-analysis was to elucidate the association between this polymorphism and the risk and mortality of sepsis. Methods: Relevant publications were searched from PubMed, EmBase, and Web of Science databases up to January 31, 2021, with studies only in Engl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Inflammation is one of the most important and basic clinical manifestations of sepsis [ 27 ]. RAW264.7 mouse macrophage line has been widely used to establish in vitro inflammation model [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation is one of the most important and basic clinical manifestations of sepsis [ 27 ]. RAW264.7 mouse macrophage line has been widely used to establish in vitro inflammation model [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…C-X-C motif chemokine ligand 8 (CXCL8), also known as interleukin-8 (IL-8), is one of the most important proinflammatory factors and plays a vital role in many inflammatory diseases including ulcerative colitis [ 4 , 5 ]. Zhao et al [ 6 ] showed that the −251 A/T polymorphism of IL-8 gene may affect the susceptibility of individuals to sepsis. Endothelin-1 (ET-1) is the most common form of ET, originally called pure vasoconstrictor, which plays an important role in the pathogenesis of different cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 99%
“…IL-8 is another proinflammatory cytokine produced by mononuclear macrophages in systemic infections. Its increase is associated with higher mortality in patients with sepsis [21]. It is also known to play a role in the progression of acute inflammatory changes within the kidney to the chronic form [22].…”
Section: Introductionmentioning
confidence: 99%